Optimalisasi Sistem Informasi Desa dalam Mewujudkan Open Government: Pendekatan Participatory Action Research - Marsista Buana Putri; Adinda Sekar Tanjung; Nela Agustin Kurnianingsih; Dian Prasetyaning Sukmawati; Aidil Afriansyah (JUKI : Jurnal Komputer dan Informatika, 2026)
Open government is a governance paradigm that places transparency, participation, and accountability as core principles, including at the village level. Indonesian Law Number 6 of 2014 on Villages, particularly Article 86, mandates every village to have a village information system accessible to the public. Neglasari Village, Katibung District, South Lampung Regency, already operates an OpenSID-based village website hosted on the smartvillage.co.id platform; however, its utilization remains suboptimal due to limited operator capacity. This research aims to optimize the OpenSID-based village information system as an instrument for realizing open government. The research employs Participatory Action Research (PAR) as the main approach, with the Waterfall development method in the implementation phase covering requirements analysis, design (use case and ERD), OpenSID configuration, testing, and maintenance. The CIPP (Context, Input, Process, Product) framework is used as a lens for interpreting findings. Testing was conducted in three dimensions: functional verification (ten black-box test scenarios), usability testing using the System Usability Scale (SUS) instrument with fourteen stakeholders, and post-launching utilization monitoring. The results show that population, correspondence services, content publication, geographic maps, population statistics, gallery, and APBDes transparency modules were successfully configured and published on the village's website domain. Nine out of ten black-box test scenarios passed fully, with one scenario passing with notes regarding internet stability. The average SUS score of 71.43 places the system in the Good category (Acceptable Grade B). Monitoring results show that 85.7% of stakeholders find the system beneficial, with the dominant constraints being limited internet connectivity and diverse digital capacity among village officials. The research concludes that participatory optimization of an OpenSID-based village information system is effective as an initial step toward realizing open government at the village level.